(3cJGH aj Yde GdWH (B( (3SDGd hLhGH (B)s - (3CHh fUQ SYjO Hf CHj GdNjQ GdeSjMji Hf YjSi GdeWHHs ((3aQfSjS HOQ LjT s)
(3ChdgG (B:s
(3HSe Gddg GdMi GdCRdi eG gh GdWH hce gi CLRGAg ? GdWH gh Yde jYQa efg CMhGd HOf GdEfSGf ef LgI eG jUM hjRhd Yf GdUMI dJMaX GdUMI GdMGUdI s
(3BNQgG (B:s
(3hjecf JOGQc eG YSGg Cf jMOK ef VQQ hgPg BNQ GdeSGFd GdWHjI GdeTJedI Ydi LeY ef Yde GdWH bUO efgG djchf eONdkG ddeHJOF hJPcQI ddefJgi hHPdc caGjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdCSFdI HGdMeQIs
(3HChdg agQS ddcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdWHs